1991
DOI: 10.1002/mrd.1080280107
|View full text |Cite
|
Sign up to set email alerts
|

Expression and activity of gamma‐glutamyl transpeptidase in the rat epididymis

Abstract: Following Northern analysis, GGT mRNA was found predominantly within the caput epididymides and kidney. The size of mRNAs for kidney, caput, corpus, and ductus deferens were 2.2, 2.3, 2.2, and 2.3 kb, respectively, whereas cauda showed a doublet of 2.2 and 2.3 kb. GGT transpeptidation and hydrolytic activity within epididymal luminal fluids collected by micropuncture showed caput = corpus greater than cauda and corpus greater than caput greater than cauda, respectively. Caput luminal GGT transpeptidation activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Glutathion (GSH) and oxidized glutathion (GSSG) are present in the epididymis (Hinton et al, 1996), as are glutathion-metabolizing enzymes such as glutathion peroxidase and gamma-glutamyl transpeptidase (GGT). These two enzymes are secreted in the proximal region, where their concentrations in the luminal fluid are the most abundant (DeLap et al, 1977;Hales et al, 1980;Kohdaira et al, 1986;Agrawal and Vanha-Perttula, 1988;Hinton et al, 1991), GPX is also associated with the sperm membrane (Jimenez et al, 1990;Perry et al, 1992).…”
Section: Proteins Involved In Sperm Protection During Storage Protectmentioning
confidence: 98%
“…Glutathion (GSH) and oxidized glutathion (GSSG) are present in the epididymis (Hinton et al, 1996), as are glutathion-metabolizing enzymes such as glutathion peroxidase and gamma-glutamyl transpeptidase (GGT). These two enzymes are secreted in the proximal region, where their concentrations in the luminal fluid are the most abundant (DeLap et al, 1977;Hales et al, 1980;Kohdaira et al, 1986;Agrawal and Vanha-Perttula, 1988;Hinton et al, 1991), GPX is also associated with the sperm membrane (Jimenez et al, 1990;Perry et al, 1992).…”
Section: Proteins Involved In Sperm Protection During Storage Protectmentioning
confidence: 98%
“…The cleavage of glutathione by GGT and the subsequent hydrolysis of cys-gly by dipeptidase enable cells to reabsorb these amino acids, thus supporting the intracellular synthesis and subsequent export of reduced glutathione [19]. Epididymal GGT has a high affinity for oxidized glutathione and is likely to play a critical role in controlling the oxidized/reduced glutathione balance to maintain concentrations of reduced glutathione capable of performing antioxidant functions within the luminal fluid [20].…”
Section: Introductionmentioning
confidence: 99%
“…GGT is a heterodimeric integral membrane glycoprotein present on the outer surface of many epithelial cells, including epididymal epithelial cells, and within epididymal luminal fluid [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several aspects of our results indicate that this exclusion was effective. For example, although γ-glutamyltransferase is in the luminal fluid throughout the epididymis, 26 it was detected only in the caput ( Figure 3A), which suggested that γ-glutamyltransferase in the luminal fluid had been removed. In addition, the results from our Northern blot analysis showed that nearly all of the selected proteins were expressed in situ.…”
Section: Discussionmentioning
confidence: 99%